2001
DOI: 10.1093/humupd/7.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal repair and post-surgical adhesion formation

Abstract: It was shown in 1919 that peritoneal healing differs from that of skin. When a defect is made in the parietal peritoneum the entire surface becomes epithelialized simultaneously and not gradually from the borders as in epidermalization of skin wounds. While multiplication and migration of mesothelial cells from the margin of the wound may play a small part in the regenerative process, it cannot play a major role, since new mesothelium develops in the centre of a large wound at the same time as it develops in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
269
0
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(283 citation statements)
references
References 31 publications
(37 reference statements)
4
269
0
10
Order By: Relevance
“…In the injured area, a gel matrix of fibrin will form and macrophages recruit new mesothelial cells over the damaged surface which reaches the reconstruction of the mesothelial lining within 5-7 days. The adhesions will take place if the surfaces damaged remain in contact [23,24]. This finding supports the idea of an ovariopexy.…”
Section: Discussionsupporting
confidence: 61%
“…In the injured area, a gel matrix of fibrin will form and macrophages recruit new mesothelial cells over the damaged surface which reaches the reconstruction of the mesothelial lining within 5-7 days. The adhesions will take place if the surfaces damaged remain in contact [23,24]. This finding supports the idea of an ovariopexy.…”
Section: Discussionsupporting
confidence: 61%
“…Studies in humans and in animal models have shown that surgical trauma initiates an inflammatory reaction that leads to deposition of a fibrin-rich matrix on peritoneal surfaces that is capable of forming attachments to adjacent viscera (11,12). If the matrix organizes into fibroblast-containing fibrin bands, permanent adhesions can form as early as 7 days after abdominal operations (13).…”
mentioning
confidence: 99%
“…[7] The two main differences are epithelization and consequences of fibrin deposition. Firstly, peritoneal epithelization takes place throughout the entire surface of the defect simultaneously.…”
Section: Discussionmentioning
confidence: 99%